Clinical stance on response initiation in autistic adults: co-creating an integrative approach based on theory and lived experiences to act from language, via motor movement to wellbeing - Greaves-Lord, Kirstin; Alma, Manna; de Graaff, Benjamin; Landsman, Jeanet; van der Weide, Klaske; Jagersma, Gabrine; Beskers, Theo; Wubs, Marieke; Mandemaker, Henri; van Daalen, Emma; van der Linde, Joost; Stapert, Anne Fleur; et al. (Frontiers in Psychology, 2023)
Getting 'stuck', literally and figuratively, is a common experience for autistic people. Literally 'stuck' means limited response initiation due to immobility with tense muscles and inability to move. Figuratively 'stuck' means loneliness, passivity or stuck in activities that do not offer long-term satisfaction. To further conceptualize this complex phenomenon of limited response initiation in autistic individuals, we performed qualitative interviews and focus groups with autistic people and their family members, followed by brainstorm sessions and a Delphi study with input from a larger panel of experts from multiple backgrounds. We aimed to co-create the outline of an integrative approach to support autistic people in moving away from this 'stuck state' to more flexible, limber 'supple states' in order to live freer, more meaningful, satisfying and peaceful lives. We here stipulate a conceptual framework, in which the described 'stuck state' at the micro-level of the muscles/behavior of one individual, probably is caused by feeling/being 'stuck' or 'cramped' at several overarching (i.e. meso and marco) levels. In this article, we discuss several types of interventive approaches (i.e. language-based talking therapies, affective experiential expressive therapies, physical therapies and systemic therapies), prevention as well as intervention programs, directed at different primary stakeholders), that can complement and enrich each other in an integrative policy, that leads to tailor-made, personalized trajectories of interdisciplinary support to enable people to live satisfying, meaningful, dignified and peaceful lives.